2012
DOI: 10.5370/jeet.2012.7.4.596
|View full text |Cite
|
Sign up to set email alerts
|

Highly transparent and resistive nanocrystalline ZnO-SnO2films prepared by rf magnetron sputtering

Abstract: -ZnO-SnO 2 films were deposited by rf magnetron sputtering using a ZnO-SnO 2 (2:1 molar ratio) target. The target was made from a mixture of ZnO and SnO 2 powders calcined at 800°C. The working pressure was 1 mTorr, and the rf power was 120 W. The ratio of oxygen to argon (O 2 :Ar) was varied from 0% to 10%, and the substrate temperature was varied from 27°C to 300°C. The crystallographic properties and the surface morphologies of the films were studied by X-ray diffraction (XRD), scanning electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Similar observation has been reported on the green synthesis of stable silver, zinc and copper oxide nanoparticles using different plant precursor (Kumara Swamy et al, 2014; Page 9 of 30 A c c e p t e d M a n u s c r i p t 9 Saware and Venkataraman, 2014). Previous works also have established that semiconducting nanoparticles exhibit dissimilarity in their electronic properties relative to the bulk counterpart (Cha et al, 2012), which was clearly observed in this study. Fig.…”
Section: Optical and Electronic Propertiessupporting
confidence: 59%
See 1 more Smart Citation
“…Similar observation has been reported on the green synthesis of stable silver, zinc and copper oxide nanoparticles using different plant precursor (Kumara Swamy et al, 2014; Page 9 of 30 A c c e p t e d M a n u s c r i p t 9 Saware and Venkataraman, 2014). Previous works also have established that semiconducting nanoparticles exhibit dissimilarity in their electronic properties relative to the bulk counterpart (Cha et al, 2012), which was clearly observed in this study. Fig.…”
Section: Optical and Electronic Propertiessupporting
confidence: 59%
“…where α is the optical absorption coefficient, hν is the photon energy, E g is the direct band gap, and E is a constant (Cha et al, 2012). Plotting (αhν) 2 as a function of photon energy and extrapolating the linear portion of the curve to zero absorption (Fig.…”
Section: Optical and Electronic Propertiesmentioning
confidence: 99%
“…The zinc tin oxide (ZTO) film was thought to be an effective active layer for TTFTs because of its wide energy band gap and high resistivity [12][13][14]. We have reported that ZTO TTFTs employing In as source/drain electrodes exhibit a mobility greater than 18.0 cm 2 /Vs [15].…”
Section: Introductionmentioning
confidence: 94%